PERANAN KOORDINASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR CAMAT KABUPATEN KUTAI KARTANEGARA - Wijayanto, Dwi (PREDIKSI, 2012)
In the effort improving officer productivity in office environment needed a effective coordination. This matter constitute the writer opinion that management function require to be in office environment in execution of bureaucrat duty give the service for public effectively and efficient. Mount the effectiveness work posed at with the productivity shall get the attention which more than the whole element of company operational. Therefore system perfection co-ordinate expected able to make the effectiveness storey;level work the employees become high. Element supporting effectiveness from the aspect of target attainment not considering target, organizational, but also its mechanism maintain the x'self and target management.This Research finds to: 1) To find answers to problems which writer open previously 2) To prove the truth of research hypothesis formulated.Pursuant toÂ  result analyse the data obtained by a the following result 1) Relation co-ordinate with the work productivity officer at Office of Sub-Regency of Anggana of Regency of Kutai Kartanegara very weak 2) Effective coordination happened officer storey, level in informal atmosphere, with the subordinate take place less be effective caused less konsisitennya head in programs work